Radiation Damage and Racemic Protein Crystallography Reveal the Unique Structure of the GASA/Snakin Protein Superfamily. Issue 28 (4th May 2016) - Yeung, Ho; Squire, Christopher J.; Yosaatmadja, Yuliana; Panjikar, Santosh; López, Gemma; Molina, Antonio; Baker, Edward N.; Harris, Paul W. R.; Brimble, Margaret A.
Abstract: Proteins from the GASA/snakin superfamily are common in plant proteomes and have diverse functions, including hormonal crosstalk, development, and defense. One 63‐residue member of this family, snakin‐1, an antimicrobial protein from potatoes, has previously been chemically synthesized in a fully active form. Herein the 1.5 Å structure of snakin‐1, determined by a novel combination of racemic protein crystallization and radiation‐damage‐induced phasing (RIP), is reported. Racemic crystals of snakin‐1 and quasi‐racemic crystals incorporating an unnatural 4‐iodophenylalanine residue were prepared from chemically synthesizedd ‐ andl ‐proteins. Breakage of the C−I bonds in the quasi‐racemic crystals facilitated structure determination by RIP. The crystal structure reveals a unique protein fold with six disulfide crosslinks, presenting a distinct electrostatic surface that may target the protein to microbial cell surfaces. Abstract : Ripping into quasiracemic crystals : The structure of the 63‐residue antimicrobial protein snakin‐1, the first structure of the GASA/snakin superfamily, has been determined using total chemical synthesis, racemic protein X‐ray crystallography, and radiation‐damage‐induced phasing. The protein adopts a unique fold containing six disulfide crosslinks and presenting a distinct electrostatic surface.